KORELASI RESILIENSI TERHADAP TINGKAT STRESS SISWA SMP BERDASARKAN USIA PADA MASA PANDEMI COVID 19 - Nur Ulmy Mahmud; Ria Qadariah Arief; Safruddin; Nurul Hikmah B (Jurnal Kesehatan, 2022)
Adolescence is a very important point in human emotional development. During the Covid-19 era, teenagers/junior high school students experienced various burdens of mental health problems that arose. .Stress that occurs at this time will affect the pattern of mental development in the future. Its influence is seen in the resilience domain. .Therefore, it is very important to analyze the correlation of Resilience to the Stress Level of Middle School Students during the Covid-19 period in Pinrang Regency, Indonesia. This study used a cross sectional study design. .The population of this research is junior high school students who live in Pinrang Regency with the number of respondents as many as 94 people. .The instrument used is the DASS 42 questionnaire (Depression Anxiety Stress scale 42) to measure stress levels and the International Resilience Project to measure student resilience. Data analysis using Pearson Correlation. .The results of this study indicate that 76.02% of students experience a very severe level of stress with a high level of resilience of 88%. .The results of the Pearson Correlation for Resilience with age are 0.175 which is positively correlated and stress levels are -0.302 which are negatively correlated. .Resilience ability in students during the Covid-19 pandemic is positively correlated with increasing age and negatively correlated with stress levels